Dual in situ crosslinking of polymer bioinks for 3D tissue biofabrication. Issue 1 (January 2017) - Thomas, Daniel J; Jessop, Zita M; Al-Sabah, Ayesha; Whitaker, Iain S
During this research, a 3D bioprinted ear structure has been produced from a hybrid gelatin and alginate bioink hydrogel. Using dual in situ crosslinking, a high-resolution bioprinted structure in the shape of the ear has been formed which is capable of maintaining live cells for 3 weeks of culture. Staining has shown the presence of cells and the formation of extracellular matrix proteins in postbioprinted tissue constructs. This research shows that chondrogenesis and successful matrix formation have occurred. This process has the potential to enhance the field of reconstructive surgery in medicine, by enabling cellular tissue constructs to be fabricated on demand through precise deposition of crosslinkable 3D biomaterials.